Application and Research Progress of High Frequency Ultrasound in the Diagnosis of Chronic Inflammatory Neuropathies - Ma, Xishun; Du, Lizhen; Yuan, Wenqing; Han, Tongliang (Frontiers in Neurology, 2022)
In recent years, clinicians have gradually improved their understanding of multiple neuropathies, and have done some studies about the chronic inflammatory neuropathies, for example, chronic inflammatory demyelinating polyneuropathy, multifocal motor neuropathy, and lewis-sumner syndrome. The early diagnosis is very important for the next step treatment and long-term prognosis. At present, the disease mainly depends on clinical and neural electrophysiological examination, but imaging studies are few. In recent years, with the rapid development of high-frequency ultrasound, it could clearly show the morphology of the nerve, and it has been an emerging diagnosis tool of polyneuropathies. This article mainly reviews the application and the latest research progress of high-frequency ultrasound in these diseases.